1993
DOI: 10.1148/radiology.187.2.8475286
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer disease: depiction of increased cerebral myo-inositol with proton MR spectroscopy.

Abstract: To define altered metabolites in the brain of patients with probable Alzheimer disease (AD) of two brain regions, localized in vivo hydrogen-1 magnetic resonance (MR) spectroscopy was performed with a short echo time (30 msec) in 11 elderly patients and 10 healthy age-matched subjects. The patients had mild to moderate dementia, assessed with standard neuropsychological tests. Two abnormalities in the patients' cerebral cortex were defined: When compared with healthy subjects, the patients showed a 22% increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
151
1
9

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(175 citation statements)
references
References 0 publications
14
151
1
9
Order By: Relevance
“…MRI studies have attempted to show specific patterns of cerebral atrophy (primarily in the temporal lobe) in patients with a clinical diagnosis of AD. In 1993, Miller et al 173 showed clear changes in MRS results in patients with AD. Their report has been followed by a host of other articles that have shown reproducible patterns of decreased NAA and increased mI in the occipital, temporal, parietal, and frontal regions of patients with AD, even at the early stages of the disease.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…MRI studies have attempted to show specific patterns of cerebral atrophy (primarily in the temporal lobe) in patients with a clinical diagnosis of AD. In 1993, Miller et al 173 showed clear changes in MRS results in patients with AD. Their report has been followed by a host of other articles that have shown reproducible patterns of decreased NAA and increased mI in the occipital, temporal, parietal, and frontal regions of patients with AD, even at the early stages of the disease.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Another metabolite that is consistently found to be abnormal in people with AD is myoinositol (mI) or mI/Cr ratio. 23,25,26 The mI peak consists of glial metabolites that are responsible for osmoregulation. 27,28 Elevated mI levels correlate with glial proliferation in inflammatory CNS demyelination.…”
mentioning
confidence: 99%
“…29 It is thought that the elevation of the mI peak is related to glial proliferation and astrocytic activation in AD. 23,25,26,30 One other metabolite peak of interest in the 1 H MRS of the brain in AD is the choline (Cho) peak. Some studies identified elevated Cho and Cho/Cr ratios, some reported normal levels in people with AD compared with normal.…”
mentioning
confidence: 99%
“…As another example, receptorinitiated phospholipase C-mediated signaling might be studied, using magnetic resonance spectroscopy to measure the brain concentration of myo-inositol, a component of the phosphoinositide cycle (35). Brain myo-inositol is elevated in diagnosed AD and in older nondemented Down syndrome subjects at risk for AD (21,41,42); it is reduced by lithium, an inhibitor of inositol monophosphatase (43).…”
Section: Small Et Almentioning
confidence: 99%